Evaluation of Educational Services Marketing Strategy in Increasing Community Interest in Al-Masthuriyah SMA School - Eneng Mia Rizkianti; Abu Bakar Ashidiqy (Budapest International Research and Critics University, 2022)
Good management is always needed to maintain business continuity so that it can always grow and develop in strategic and operational decisions of the company. strategy for determining the market and targeting of educational services, strategy for determining market positioning for educational services and marketing mix strategy for education services (marketing mix) at Al-Masthuriyah high school (SMA) which is located on Jl. Raya Cibolang KM 7 No. 03 Rt. 49/10 Dec. Cibolang kaler Kec. Cisaat Kab. Sukabumi zip code (43152). In this study the authors wanted to know how the evaluation of the service marketing strategy carried out by Al-Masthuriah High School, how the students' responses regarding the educational services owned by Al-Masthuriyah High School and this research is a descriptive qualitative approach with data analysis and data collection techniques through observation, interviews, documentation and literature. The results of the data processing research show that the marketing strategy has a significant effect on the level of public trust in educational services and is inversely proportional if the school does not carry out a marketing strategy, there is a lack of student interest in the school because they are not familiar with the school.